Comparative Performance Analysis of Traditional (SFQ, PCQ) and Modern (FQ-CoDel, CAKE) Queuing Algorithms on MikroTik RouterOS v7 for Broadband Network QoS Optimization - Maulana, OK Muhammad Majid; Asrianda; Muhammad Fikry (Teewan Journal Solutions, 2025)
Bufferbloat in broadband networks often leads to high latency, which degrades the Quality of Experience (QoE), particularly for time-sensitive activities. MikroTik RouterOS v7 introduces modern Active Queue Management (AQM) algorithms, such as FQ-CoDel and CAKE, which are claimed to outperform traditional algorithms like SFQ and PCQ. This study aims to analyze and compare the performance of these four queuing algorithms in a single-link gateway scenario on a 35 Mbps internet service. The research methodology employs a quantitative experimental approach by saturating the network with heavy traffic. Quality of Service (QoS) parameters including throughput, delay, jitter, and packet loss—were measured based on TIPHON standards. The results indicate that modern algorithms maintain latency stability under full load significantly better than traditional ones. This study recommends the use of FQ-CoDel for resource efficiency and CAKE for maximum quality